Analysis of the Causes of the Decline in Water Production Bid on Fresh Water Generator in Ship MV. Lumoso Karunia II - Syahputra, Ferdyan Alam; Daryanto, Daryanto; Saktiono, Maxima Ari (Universitas Hang Tuah, 2024)
This study aims to analyze the causes of the decline in fresh water production on the Fresh Water Generator on the MV. Lumoso Karunia II. Researchers conducted this research for 12 months and 5 days conducted on the MV. Lumoso Karunia II which is a type of Bulk Carrier ship which is a ship owned by PT Lumoso Pratama Line Company. This research method uses quantitative methods. Researchers use secondary data in the form of library books, journals and documents related to this research, while primary data in this study is in the form of direct field studies. Data collection techniques in this study are library research, direct and indirect observation and interviews. The results of this study indicate that the performance of the fresh water generator auxiliary aircraft is less than optimal so that what is produced does not match the amount of capacity due to lack of maximum maintenance. With the thickness of scale attached to the evaporator pipe of 1.85 mm, it causes blockage of the evaporator pipe. Thus, there is a decrease in intake in the evaporator. So, the decrease in intake in the evaporator resulted in a decrease in fresh water production of 16 m3 tons in the fresh water generator. As a result of the decrease in fresh water production in the fresh water generator at MV. Lumoso Karunia II is a shortage of fresh water in accommodation and disruption of the cooling process in machinery.